Influence of Apathy on Executive Functioning in Patients with Idiopathic Parkinson's Disease without Dementia (2024)
To determine the influence of apathy on executive functioning in patients with Idiopathic Parkinson's Disease Without Dementia (IPD Without Dementia) in stages I and II of the Hoehn and Yahr scale. Apathy is a common neuropsychiatric pathology in IPD Without Dementia. It is characterized by decreased motivation and inability to perform tasks involving immediate behavioral organization and direction.